GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 437 species occurrences available in GBIF matching the query: TaxonKey: Barrosoa betonicaeformis (DC.) R.M.King & H.Rob.. The dataset includes 437 records from 43 constituent datasets: 1 records from HUEM - Herbário da Universidade Estadual de Maringá. 6 records from HUFU - Herbarium Uberlandense. 5 records from IAC - Herbário do Instituto Agronômico de Campinas. 17 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 17 records from Naturalis Biodiversity Center (NL) - Botany. 2 records from SPSF - Herbário Dom Bento José Pickel. 11 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 14 records from ICN - Herbário do Instituto de Ciências Naturais. 13 records from MBM - Herbário do Museu Botânico Municipal. 1 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 84 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 1 records from FCAB - Herbário Friburguense. 1 records from HUCS - Herbário da Universidade de Caxias do Sul. 1 records from HUSC - Herbário Unisanta. 1 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 1 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 4 records from EFC - Herbário Escola de Florestas Curitiba. 1 records from UEC - Herbário da Universidade Estadual de Campinas. 1 records from Missouri Botanical Garden. 3 records from Natural History Museum (London) Collection Specimens. 1 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 1 records from Botanical Museum, Copenhagen. Database of type specimens. 1 records from CVRD - Herbário da Reserva Natural Vale. 3 records from Field Museum of Natural History (Botany) Seed Plant Collection. 2 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 1 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 19 records from UPCB - Herbário do Departamento de Botânica. 5 records from HURB - Herbário do Recôncavo da Bahia. 1 records from HVAT - Herbário do Vale do Taquari. 77 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from FURB - Herbário Dr. Roberto Miguel Klein. 2 records from HAS - Herbário Alarich Rudolf Holger Schultz. 1 records from EAC - Herbário Prisco Bezerra. 1 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 27 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 2 records from R - Herbário do Museu Nacional. 25 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 5 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 1 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 3 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 12 records from Instituto de Botánica Darwinion. 6 records from HRCB - Herbário Rioclarense. 54 records from PACA-AGP - Herbarium Anchieta.
Keywords: GBIF; biodiversity; species occurrences